Gender issues in cooperatives - Nakkiran, S. (Discovery Publishing House, 2012)
This book has two parts. Part 1 deals with general concepts on gender issues. Part II is devoted for gender issues in cooperatives covering topics on place of women in cooperatives and their participation, gender integration, legal constraints, suitable women cooperatives, and role of ICA.